Agreement between parents and adolescents on dental fluorosis: a population-based study - Maria Eneide Leitão de Almeida; Ana Karine Macedo Teixeira; Carlos Henrique Alencar; Saul Martins Paiva; Mauro Henrique Nogueira Guimarães de Abreu (Sociedade Brasileira de Pesquisa Odontológica, 2013)
This study evaluated the prevalence and severity of dental fluorosis and compared the reports from adolescents aged 12 to 18 years with those of their parents regarding the perceptions and concerns arising from this disease. The study was conducted in the cities of Viçosa and Sobral and the District of Rafael Arruda (Sobral), Ceará. A cross-sectional study was conducted from October 2010 to March 2011, with 891 students examined and 780 parents or guardians interviewed. Dental fluorosis was measured using the Dean's Index, and the Child's and Parent's Questionnaire about Teeth Appearance was used to assess the reports from parents and adolescents. A chi-squared test for trends was used to compare the opinions of parents and adolescents about fluorosis, and the agreement was measured using the weighted kappa. For the dichotomous variables, we used the unweighted kappa coefficient. The prevalence of fluorosis was 29.7%, but in the District of Rafael Arruda, evidence of very mild and mild fluorosis was found in 32.5% of the subjects, and moderate and severe fluorosis was found in 28.7%. There was poor agreement between the data reported by the adolescents and their parents or guardians regarding areas of concern and their perceived satisfaction with the appearance and color of their teeth. The prevalence of dental fluorosis was high in one of the communities studied, but the clinical diagnosis of this condition should not necessarily equate with concern and dissatisfaction with aesthetic appearances among teenagers and their parents.